Residential Segregation, School Segregation and Vulnerability by National Origin: A Case Study in Granada, Spain - Lubián Graña, Carlos (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This paper analyses the link between residential and school segregation of immigrant students in Granada. We use microdata of foreign resident population and students enrolled in primary school, during the 2014-15 academic course. We apply a geographical methodology (GIS) to show three case studies of highsegregated- schools crossing data with vulnerability indicators in the territory.The results suggest, first, high levels of segregation in the city; second, school segregation is higher than residential segregation, which is important to show that segregation process could not be totally explained by residential location; third, case studies show that specific nationalities tend to concentrate in certain schools and not necessarily due to proximity.
Keywords: immigration; catchment areas; segregation; school mapping